2018
DOI: 10.1038/s41440-018-0144-z
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota and inflammation in chronic kidney disease and their roles in the development of cardiovascular disease

Abstract: The health and proper functioning of the cardiovascular and renal systems largely depend on crosstalk in the gut-kidney-heart/vessel triangle. Recent evidence suggests that the gut microbiota has an integral function in this crosstalk. Mounting evidence indicates that the development of chronic kidney and cardiovascular diseases follows chronic inflammatory processes that are affected by the gut microbiota via various immune, metabolic, endocrine, and neurologic pathways. Additionally, deterioration of the fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 251 publications
(426 reference statements)
1
72
0
1
Order By: Relevance
“…In a recent meta-analysis, the incidence of acute kidney injury in AIS patients reached up to 9.6%, and was associated with increased overall mortality rate ( 96 ), in-hospital mortality, and neurological deterioration ( 97 ). Uremic toxins are waste products of microbiota that can cross the intestinal blood–barrier because of increased gut permeability after AIS, and thus reach the systemic circulation ( 98 ). In support of a purported gut–brain–kidney axis, an experimental study demonstrated that rats affected by both acute kidney injury and AIS displayed neuronal loss; glial, macrophage, and microglial upsurge; and increased circulating IL-6 and IL-1β levels ( 99 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis, the incidence of acute kidney injury in AIS patients reached up to 9.6%, and was associated with increased overall mortality rate ( 96 ), in-hospital mortality, and neurological deterioration ( 97 ). Uremic toxins are waste products of microbiota that can cross the intestinal blood–barrier because of increased gut permeability after AIS, and thus reach the systemic circulation ( 98 ). In support of a purported gut–brain–kidney axis, an experimental study demonstrated that rats affected by both acute kidney injury and AIS displayed neuronal loss; glial, macrophage, and microglial upsurge; and increased circulating IL-6 and IL-1β levels ( 99 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microbiota is also involved in the CKD-related systemic complications such as cardiovascular diseases, uremic sarcopenia, and mineral bone disorders [ 8 , 9 , 10 ]. The effects along the gut-kidney axis mainly involve metabolic and immune pathways [ 1 , 11 , 12 ]. The microbiota presents both positive and negative metabolic effects, since it is responsible for producing beneficial metabolites in kidney diseases such as short-chain fatty acids [ 13 , 14 ] and harmful metabolites such as uremic toxins [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most Proteobacteria and some Firmicutes family produce pro-inflammatory uremic toxins [81, 82], while Lactobacilli produce anti-inflammatory mediators, including short-chain fatty acid (SCFA) and NO [83, 84]. SCFAs increase anti-inflammatory gut hormones, including GLP-1, GLP-2, and PYY from enteroendocrine cells [83].…”
Section: Gastrointestinal Tract and Bp Regulationmentioning
confidence: 99%